Length–weight and length–length relationships of seven freshwater fish species from the Daning River, a tributary of the Yangtze River, southwest China. (19th December 2017) - Chen, X. W. J.; An, M.; Tang, H. Y.; Cao, H. Y.; Yang, Z.
Summary: This study determined the length–weight relationships (LWRs) and length–length relationships (LLRs) of seven freshwater fish from the Daning River, a tributary of the Yangtze River, southwest China. Specimens were collected between July 2016 and July 2017 using drift gill nets (mesh size 1, 2 and 3 cm), cage net (0.5 cm mesh size) and electroshock fishing techniques quaterly. Parameter b values of LWRs ranged from 2.647 to 3.276 ( r 2  > .963) and b values of LLRs ranged from 1.091 to 1.213( r 2  > .985). Six new LLRs and seven new maximum length data are presented. The biometric data and their relationships are relevant to Fishers science to supplement other data sets needed for fisheries management.